Viscosity temperature properties from molecular dynamics simulation: The role of calcium oxide, sodium oxide and ferrous oxide. (1st February 2019) - Dai, Xin; Bai, Jin; Huang, Qing; Liu, Zhen; Bai, Xiaojing; Cao, Ronggen; Wen, Xiaodong; Li, Wen; Du, Shiyu
Abstract: For the long-term stable operation of the entrained flow gasifier in the coal chemical industry, the flux agents are generally adopted to adjust the fusibility of coal ash. Therefore, it is necessary to understand the underlying mechanism for the impact of typical oxide flux agents on viscosity temperature properties of coal ash from structures and thermodynamics. In this work, the role of calcium oxide, sodium oxide and ferrous oxide on viscosity temperature properties is investigated by a combination of molecular dynamics simulations and thermodynamic calculations. The variations of viscosity and temperature of critical viscosity are obtained for different ternary coal ash systems by thermodynamic calculation. Ternary phase diagrams are applied to evaluate the effect of different flux agents, which are also found to cause mineral transformation from high-temperature minerals to low-temperature minerals. Oxygen bond species are employed as the indicator of the structural evolution originating from addition of different flux agents. The sodium atoms may more readily weaken the tricluster oxygen bonds than calcium or ferrous atoms according to the results. Higher content of bridging oxygen bonds in the sodium oxide ternary coal ash system can enhance the stability of the structures and induce higher viscosity. Stability coefficients are defined here and a function to describe the relationship between the viscosity and flux agent content is established. The results from the current work are expected to provide new clues to find strategies controlling the fusion behaviour of coal ash systems.